2015
DOI: 10.1097/brs.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

A Global Perspective on the Outcomes of Surgical Decompression in Patients With Cervical Spondylotic Myelopathy

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
157
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(168 citation statements)
references
References 36 publications
6
157
1
4
Order By: Relevance
“…While in the past the documentation of improved clinical outcomes using patient-reported outcome has proved challenging, 14 more recent studies have reported improvements after spine surgery with patient-reported outcome measures. 2,3,6,8,11,15,[19][20][21]25,30 Some may argue that clinical outcome following surgery for DCM is best assessed by a disease-specific measure of neurological disability such as the modified Japanese Orthopaedic Association (mJOA) scale score. While widely reported in the literature, the mJOA is an investigator-administered tool, not a patientreported outcome, and may have poor discrimination in predicting clinical outcome from the perspective of the patient.…”
mentioning
confidence: 99%
“…While in the past the documentation of improved clinical outcomes using patient-reported outcome has proved challenging, 14 more recent studies have reported improvements after spine surgery with patient-reported outcome measures. 2,3,6,8,11,15,[19][20][21]25,30 Some may argue that clinical outcome following surgery for DCM is best assessed by a disease-specific measure of neurological disability such as the modified Japanese Orthopaedic Association (mJOA) scale score. While widely reported in the literature, the mJOA is an investigator-administered tool, not a patientreported outcome, and may have poor discrimination in predicting clinical outcome from the perspective of the patient.…”
mentioning
confidence: 99%
“…3,19,20 Based on two recent prospective studies, patients, on average, exhibited a 2.40-to 2.88-point gain on the modified Japanese Orthopaedic Association (mJOA) scale following surgery, an improvement exceeding the overall MCID for this metric (2 points). 2,5,8,28 The MCID of the mJOA scale, however, varies based on preoperative myelopathy severity: 1 point for mild myelopathy (mJOA ≥ 15), 2 points for moderate myelopathy (mJOA score of [12][13][14], and 3 points for severe disease (mJOA score < 12). 28 Before undergoing surgery, patients are likely to inquire about the ultimate goals of the operation and of their chances of experiencing meaningful improvements in functional status.…”
mentioning
confidence: 99%
“…5,8 In general, surgical decompression of the cervical spine is effective at halting neurological deterioration, relieving certain symptoms, and improving functional status and quality of life. The minimum clinically important difference (MCID) is defined as the minimum change in a measurement that a patient would identify as beneficial.…”
mentioning
confidence: 99%
“…Koji Tamai 1) , Hidetomi Terai 1) , Akinobu Suzuki 1) , Hiroaki Nakamura 1) , Masaomi Yamashita 2) , Yawara Eguchi 3) , Shiro Imagama 4) , Kei Ando 4) , Kazuyoshi Kobayashi 4) , Morio Matsumoto 5) , Ken Ishii 5) , Tomohiro Hikata 5) , Shoji Seki 6) , Masaaki Aramomi 7) , Tetsuhiro Ishikawa 7) , Atsushi Kimura 8) , Hirokazu Inoue 8) , Gen Inoue 9) , Masayuki Miyagi 9) , Wataru Saito 9) , Kei Yamada 10) , Michio Hongo 11) , Kenji Endo 12) , Hidekazu Suzuki 12) , Atsushi Nakano 13) , Kazuyuki Watanabe 14) , Junichi Ohya 15) , Hirotaka Chikuda 15) , Yasuchika Aoki 16) , Masayuki Shimizu 17) , Toshimasa Futatsugi 17) , Keijiro Mukaiyama 17) , Masaichi Hasegawa 18) , Katsuhito Kiyasu 19) , Haku Iizuka 20) , Kotaro Nishida 21) , Kenichiro Kakutani 21) , Hideaki Nakajima 22) , Hideki Murakami 23) , Satoru Demura 23) , Satoshi Kato 23) , Katsuhito Yoshioka 23) , Takashi Namikawa 24) , Kei Watanabe 25) …”
Section: Risk Factors Of Cervical Surgery Related Complications In Paunclassified
“…As the population ages, the number of patients with degenerative spinal diseases, such as cervical spondylotic myelopathy (CSM), is increasing. Some may need surgery at around 80 years old in severe cases [2][3][4] owing to recent advances in surgical techniques and general anesthesia. Furthermore, clinical results of surgery for the aged population were reported to not be inferior compared to that in young patients 5,6) .…”
Section: Introductionmentioning
confidence: 99%